STATUS GIZI IBU MENYUSUI DAN KADAR IODIUM DALAM AIR SUSU IBU DI DAERAH DENGAN NILAI EKSKRESI IODIUM URIN TINGGI - Sri Supadmi; Yusi Dwi Nurcahyani; Asih Setyani (Media Gizi Mikro Indonesia, 2017)
Results of a survey conducted in 2003 found 35% of women had urinary iodineexcretion is more than 300 μg/L that can harm our health at risk. Nutritional statusof breastfeeding mothers may affect the value of iodine levels in ation due tomaternal nutritional status of underweight or malnutrition can lead to impairedmilk production, more rapid exit and urine iodine levels in urine is reduced. Toknow the nutritional status of lactating mothers correlation with levels of iodine inbreast milk (ASI) in areas with high urinary iodine excretion values. The study wasconducted in the District of Demak, Central District of Coral as areas that havehigh urinary iodine excretion values. Cross Sectional research design. This type ofresearch is applied research. Samples: breastfeeding mothers aged 17-45 years.Large samples were calculated based on the sample to the relationship betweentwo variables with one-sided test of significance (a1) = 0.05, r = 0.2 and power= 80. Random sampling (simple random sampling) during lactation according toinclusion criteria. Univariabel analysis includes data analysis, correlation analysis.Most of the father’s occupation as a farmer 20.0%. This type of work more than30% of mothers did not work, father and mother education level is the most widelydad graduated from elementary school to 27.6% for women 29.4%. Nutritionalstatus of breastfeeding mothers by BMI is normal nutritional value as much as73.03%. nutritional status based on the value of upper arm circumference (lilac) isnormal as many as 73.33%. Iodine levels in mother’s milk (ASI) was also high at97% above normal or ≥ 300 mg / l. The correlation between the type of work withthe levels of iodine in ation coefficient has a value of 0.458 and p value <0.05.There is no correlation between maternal nutritional status through measurementof lilac, with BMI levels of iodine in breast milk. Only on the type of work motherwho has a correlation with the levels of iodine in breast milk.